2021
DOI: 10.1016/j.jinf.2020.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early application of social distancing interventions on COVID-19 mortality over the first pandemic wave: An analysis of longitudinal data from 37 countries

Abstract: Covid-19 Sars-cov-2 2019-ncov Severe acute respiratory syndrome coronavirus 2 s u m m a r y Objectives: To estimate the effect of early application of social distancing interventions on Covid-19 cumulative mortality during the first pandemic wave. Methods: Ecological longitudinal study using multivariable negative binomial regression for panel data. Daily numbers of Covid-19 cases and deaths, and data on social distancing interventions, for the 37 member countries of the Organization for Economic Cooperation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 30 publications
3
103
0
Order By: Relevance
“…Other research has highlighted the importance of the timing of control measures in mitigating the COVID-19 pandemic. One study of the 37 Organization of Economic Cooperation and Development member countries found that implementing school closures and gathering bans 1 week earlier could have reduced mortality by 44% ( 7 ). A modeling study highlighted a “window of opportunity” for implementing social distancing directives, suggesting that even small delays could lead to much higher incidence rates ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has highlighted the importance of the timing of control measures in mitigating the COVID-19 pandemic. One study of the 37 Organization of Economic Cooperation and Development member countries found that implementing school closures and gathering bans 1 week earlier could have reduced mortality by 44% ( 7 ). A modeling study highlighted a “window of opportunity” for implementing social distancing directives, suggesting that even small delays could lead to much higher incidence rates ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding the transmission dynamics and clinical characteristics of SARS-CoV-2 infection in children have suggested that children may become a significant spreader at the explosion stage of the outbreak [ 66 ], while at the same time the risk of diffusion of infection from child to child is low and even the transmission from a child to an adult is uncommon [ 67 , 68 , 69 ]. Moreover, as Piovani et al suggest [ 70 ], combination of mass gathering bans and school closures is associated with the reduction in COVID-19 mortality. In this study, we sought to investigate the effect of school closure in MTCs patterns.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic many congresses are being cancelled to avoid gatherings of hundreds or thousands of attendees in a single venue [1]. These decisions might have signi cant consequences as medical education is being disrupted; also economic damage to scienti c societies and industry partners has to be expected.…”
Section: Discussionmentioning
confidence: 99%